2018
DOI: 10.3389/fncel.2018.00331
|View full text |Cite
|
Sign up to set email alerts
|

Prominent Changes in Cerebro-Cerebellar Functional Connectivity During Continuous Cognitive Processing

Abstract: While task-dependent responses of specific brain areas during cognitive tasks are well established, much less is known about the changes occurring in resting state networks (RSNs) in relation to continuous cognitive processing. In particular, the functional involvement of cerebro-cerebellar loops connecting the posterior cerebellum to associative cortices, remains unclear. In this study, 22 healthy volunteers underwent a multi-session functional magnetic resonance imaging (fMRI) protocol composed of four conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 75 publications
6
32
0
Order By: Relevance
“…Recently, using advanced tractography, it has been possible to reconstruct the tracts wiring the cerebral cortex and the cerebellum demonstrating the existence of cerebro-cerebellar loops involving the associative areas ( Palesi et al, 2015 , 2017b ). Moreover, resting-state fMRI (rs-fMRI) has demonstrated that the cerebellum is entrained into large-scale coherent oscillations together with cerebral cortical regions to form several resting-state networks, including the default-mode network, salience network and attention network in addition to the sensorimotor network ( Buckner, 2013 ; Castellazzi et al, 2018 ). Finally, task-dependent fMRI has shown cerebellar activation, together with several cerebral cortical areas, during the execution of motor and cognitive tasks ( Casiraghi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, using advanced tractography, it has been possible to reconstruct the tracts wiring the cerebral cortex and the cerebellum demonstrating the existence of cerebro-cerebellar loops involving the associative areas ( Palesi et al, 2015 , 2017b ). Moreover, resting-state fMRI (rs-fMRI) has demonstrated that the cerebellum is entrained into large-scale coherent oscillations together with cerebral cortical regions to form several resting-state networks, including the default-mode network, salience network and attention network in addition to the sensorimotor network ( Buckner, 2013 ; Castellazzi et al, 2018 ). Finally, task-dependent fMRI has shown cerebellar activation, together with several cerebral cortical areas, during the execution of motor and cognitive tasks ( Casiraghi et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that there was a significant involvement of the cerebellar Crus I/II (bilaterally) in FTLD compared to ALS, could partially explain the cognitive impairment of these patients given the role of this region in memory and language processing 27 as well in continuous cognitive processing tasks. 17 Furthermore, our study shows a statistically significant involvement of the posterior cerebellum in FTLD compared to ALS, which could point to a greater disruption of the cerebro-cerebellar circuit in FTLD. This is further supported by the atrophy found in the ATR, which is known to be part of the efferent pathway from the superior cerebellar peduncle.…”
Section: All the Above Was Discussed In Terms Of Comparison Between Pmentioning
confidence: 54%
“…This result is consistent with recent literature showing more and more often that the cerebellum has a key role in cognition and in supporting advanced functions. 31,32,17 Furthermore, recent studies have reported the presence of a high proportion of cerebellar connections with the frontal and prefrontal cortex 29 consistent with the fact that the FAB is thought to require predominantly frontal and prefrontal cortex and more generally high-level functions. Indeed, Crus I is known to be involved in cognition, whereas lobule VII has recently been shown to have a role in cognitive and social behavior, with particular focus on persisting behavior and novelty seeking.…”
Section: All the Above Was Discussed In Terms Of Comparison Between Pmentioning
confidence: 66%
See 1 more Smart Citation
“…In brief, they proposed that “the primary purpose for which the phonological loop evolved was to store unfamiliar sound patterns while more permanent memory records are being constructed” (abstract). Following the findings of Ashida, Cerminara, Edwards, Apps and Brooks [33] , Castellazzi, Bruno, Toosy, Casiragi, Palesi, Savini et al [39] , Crespi, Read & Hurd [34] and Saeki, Baddeley, Hitch and Saito [40] , it is reasonable to suggest that new, repetitious words would be error-corrected and modeled in the cerebellum in relation to existing phonological working memory. These findings provide a direct neurological parallel to Baddeley, Gathercole and Papagno's description of the purpose and operation of the phonological loop for acquisition of new word forms, a scenario that within Vandervert's [23] , [41] proposals places the evolutionary origin of the phonological loop as a concomitant to new, fast-paced cerebellar attention shifting [42] among and internal modeling of new, repetitious movement requirements and counterpart inner vocalizations across the evolution of stone-tool making.…”
Section: Introductionmentioning
confidence: 80%